2007
DOI: 10.2807/esm.12.06.00719-en
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks of monophasic Salmonella enterica serovar 4,[5],12:i:- in Luxembourg, 2006

Abstract: 12 · I ss u es 3 -6 · A p r -J u n 20 07 · w w w. e uros urve ill an c e . o rg O u t b r e a k r e p o r t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 3 publications
1
79
1
1
Order By: Relevance
“…enterica serotype 4,5,12:i-monophasic is a common cause of food-borne illness in Spain and is believed to be associated with contaminated pork (Echeita et al, 1999;Astorga, et al, 2007). This serotype has also been found to be a cause of food-borne illnesses in New York, New York, USA, and in Luxembourg (Agasan et al, 2002;Anavisit et al, 2005;Mossong et al, 2007). The isolates in all of these outbreaks differed from the 4,5,12:i-monophasic isolates in this study as they all demonstrated resistance to multiple antibiotics.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…enterica serotype 4,5,12:i-monophasic is a common cause of food-borne illness in Spain and is believed to be associated with contaminated pork (Echeita et al, 1999;Astorga, et al, 2007). This serotype has also been found to be a cause of food-borne illnesses in New York, New York, USA, and in Luxembourg (Agasan et al, 2002;Anavisit et al, 2005;Mossong et al, 2007). The isolates in all of these outbreaks differed from the 4,5,12:i-monophasic isolates in this study as they all demonstrated resistance to multiple antibiotics.…”
Section: Discussioncontrasting
confidence: 47%
“…The Spanish isolates were DT U302 (Astorga et al, 2007). The Luxembourg isolates were DT 193, giving them the same determinate type as the common S. enterica serotype 4,5,12:imonophasic isolates from the Cattle Egrets (Mossong et al, 2007). Although the Cattle Egret 4,5,12:i-monophasic isolates are distinguishable by antibiotic resistance patterns or determinate type from those causing disease in people, the chick-infection trials suggest that they are potential zoonotic pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Monophasic S. Typhimurium strains have been reported from pigs, cattle, poultry and humans (de la Torre et al 2003;Sorensen et al, 2002;Zamperini et al 2007). There have been food-borne outbreaks involving this strain in humans in MSs and non-European countries (Agasan et al 2002;Tavechio et al 2004;Amavisit et al 2005;Mossong et al 2007). The strain was also commonly reported in the EU-wide baseline surveys of slaughter and breeding pigs that were carried out in 2006until 2008(EFSA, 2008EFSA 2009c).…”
Section: Prevalence Of Salmonella-contaminated Broiler Carcassesmentioning
confidence: 99%
“…Monophasic S. Typhimurium has been considered a new pandemic strain of Salmonella in Europe, typically showing resistance to four antimicrobials (ampicillin, streptomycin, sulfonamides and tetracyclines) (Mossong et al, 2007;Hopkins et al, 2010). Many isolates are genetically related and, of definitive phage types, DT120 or DT193 and have been detected in several European countries, with pigs considered the likely reservoir of infection.…”
Section: Resistance Levels In Salmonella Typhimuriummentioning
confidence: 99%